Predicting The Outcome Of A Contract Ratification Vote - Martin, James E.; Berthiaume, Ruth D. (Academy of Management Journal, 1995)
This study examined the role of employee assessments of psychological and material factors in predicting the outcome of a contract ratification vote. The results show that both the material aspects of the contract settlement at hand and how members feel about their union and their jobs have an important impact on the ratification outcome.